Association of Metabolic Obesity Phenotypes and Total Testosterone in Chinese Male Population - Liu L (Dove Medical Press, 2021)
Luna Liu,1,2 Shuang Liu,1,2 Qianmei Song,1,2 Dandan Luo,1,2 Yu Su,1,2 Xiangyu Qi,1,2 Qian Wang,3 Jing Ning,1,2 Youyuan Lv,1,2 Qingbo Guan1,2,4 1Department of Endocrinology, Shandong Provincial Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong 250021, People’s Republic of China; 2Shandong Provincial Key Laboratory of Endocrinology and Lipid Metabolism, Institute of Endocrinology and Metabolism, Shandong Academy of Clinical Medicine, Jinan, Shandong 250021, People’s Republic of China; 3Department of Ultrasound, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong 250021, People’s Republic of China; 4Department of Endocrinology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong 250021, People’s Republic of ChinaCorrespondence: Qingbo Guan Tel +86-531-68776375Fax +86-531-87068707Email doctorguanqingbo@163.comObjective: Obesity and metabolic syndrome have been reported to exert an impact on the male reproductive system with decreasing levels of serum total testosterone (TT); however, the effect of different metabolic obesity phenotypes on testosterone has been poorly studied. We aimed to evaluate the association of metabolic obesity phenotypes and total testosterone levels in a Chinese male population.Methods: We performed a retrospective study based on an epidemiological investigation, a total of 4,081 male individuals aged from 40– 75 years old were recruited. The population was classified as metabolically healthy normal weight (MHNW), metabolically healthy overweight/obese (MHO), metabolically unhealthy normal weight (MUNW), and metabolically unhealthy overweight/obese (MUO) according to normal weight (BMI< 25.0) and overweight/obesity (BMI≥ 25.0) with or without metabolic syndrome.Results: We collected 563 hypotestosteronemia among 4,081 male individuals. The odds ratios (ORs) (95% CIs) of hypotestosteronemia in obesity and metabolic syndrome were 3.072 (2.414– 3.911) and 3.294 (2.631– 4.125), respectively, after adjusting for age, luteinizing hormone, smoking status, and alcohol consumption. Compared to the MHNW group, male subjects in MHO, MUNW, and MUO groups had decreased serum TT levels. Additionally, the MUO group had a lowest concentration of serum TT and a highest proportion of hypotestosteronemia. There was no significant difference of TT levels between the MHO and MUNW groups.Conclusion: Obesity and metabolic syndrome are independent risk factors of hypotestosteronemia in Chinese male populations. Our study also suggested that individuals with MHO, MUNW, and MUO have a higher risk of developing hypotestosteronemia.Keywords: metabolic obesity phenotypes, testosterone, metabolically healthy overweight/obese, metabolically unhealthy normal weight, hypotestosteronemia